Rumah Budaya Anggrunggondok sebagai Sarana Membangun Lokalitas Gereja di Keuskupan Purwokerto, Jawa Tengah - Antonius Galih Arga Wiwin Aryanto; Agustinus Brian Kurniawan; Saptono (Asosiasi Teolog Indonesia, 2023)
This article examines the Anggrunggondok cultural house (rumah budaya) as a space of meeting and mutual dialogue between local Javanese values and the Catholic Church, through gamelan, ketoprak, and other traditional Javanese arts. The cultural house is located in Anggrungondok, Kapencar, Wonosobo, Central Java in the Diocese of Purwokerto. Research was conducted by means of in-depth interviews with resident artists. Study findings demonstrate the benefits of the cultural house as an instrument for the Church to develop the local community and become more relevant and significant for people nearby. The Anggrunggondok cultural house does this by helping farmers to be more self-supporting and artists to develop their local culture.